STRENGTHENING VILLAGE EQUIPMENT CAPACITY THROUGH AQUAPONIC CATFISH CULTIVATION IN LAMGAPANG VILLAGE, ACEH BESAR - Wahyu Ario Pratomo; Chenny Seftaria; Inggrita Gusti Sari Nasution; Monika Andrasari (RADJA PUBLIKA, 2023)
Lamgapang Village in Krueng Barona Jaya District, Aceh Besar Regency, faces economic challenges due to the conversion of agricultural land into residential areas. Many local residents have lost their jobs in the agricultural sector, with only a few continuing small-scale businesses. The COVID-19 pandemic has further worsened their economic conditions. To help improve the community's welfare, this community service program aims to develop catfish farming using an aquaponic system. Catfish was chosen because it is the most popular fish and widely sold in traditional markets, including in Aceh, as well as being affordable and easily accessible to the public. This aquaponic system not only optimizes catfish production but also provides additional yields in the form of fresh vegetables that can be consumed or sold to generate extra income. Through this program, it is hoped that the economy of the residents of Lamgapang Village will improve significantly.